Investigation and Validation of Detection of Storage Stability of Difenoconazole Residue in Mango. (1st April 2019) - Zhao, Fangfang; Liu, Jingkun; Han, Bingjun; Luo, Jinhui
Abstract : To investigate the stability of the pesticide residue in storage samples is a part of detection, which is also an improvement to the accuracy of analytical results. In this work, the UPLC-MS/MS method with perfect accuracy and stability was established for determining residues of difenoconazole in mango. The stability of the residue under different temperatures (4°C and −20°C) and media (fruit samples and pretreated sample solution) was investigated. At 0.1 mg/kg, the residue degraded in 6 months by 12% when at −20°C, while in a week by only 12.2% at 4°C. However, when pretreated and preserved in the solution, the residue remained more than 90% for 6–8 weeks. The results indicated that the main causes of degradation are biochemical factors, and the factors are affected by temperature. The findings also provided appropriate conditions for sample storage. This investigation promotes the accuracy in detection and hence guarantees food safety and quality.